Genetic counseling: A survey to explore knowledge and attitudes of Italian nurses and midwives. (19th October 2012) - Godino, Lea; Turchetti, Daniela; Skirton, Heather
Abstract In the past, genetic services were delivered to a limited number of families with rare conditions. However, genomics is now being applied to both inherited and common diseases in a range of healthcare settings, and there is a greater need for nurses to understand the basic concepts of genetic health care. The aim of this cross‐sectional survey was to explore the understanding and attitudes of Italian nurses toward genetic health care. A questionnaire was completed by 102 nurses and midwives (85% response rate). Of these, 61% believed that genetic counseling was only an informative and advisory process, and 53.9% could not specify to whom the counseling was aimed. When asked to identify nurses' role in genetic health care, 62% of the respondents believed they had no role, although 28% believed that nurses could provide information, support, and counseling. These findings indicate that nurses have only partial knowledge of the issues surrounding genetic health care. To prepare nurses for the post‐genomic era, improved genetic education at the undergraduate and postgraduate levels is required.